Exploring the effects of IFN-τ on LPS-induced endometritis in cows based on transcriptomics - Pan Liu; Yaofeng Zhang; Xu Chen; Lijun Tang; Wenxiu Xu; Guigui Wang; Duoqi Zhang; Junfeng Liu (PLoS ONE, 2026)
Endometritis in dairy cows is a common reproductive disease that severely affects reproductive performance and milk production, resulting in significant economic losses. Lipopolysaccharide (LPS) as a PAMP capable of inducing inflammatory responses in the endometrium through the NF-κB pathway. Interferon-tau (IFN-τ) is a type I interferon with significant anti-inflammatory properties. Currently, transcriptomics sequencing technology has gradually become an attractive tool for studying such diseases. This study established an inflammatory model of bovine endometrial cells (BENDs) using LPS induction and employed RNA-seq technology to investigate the expression profiles of mRNAs in BENDs from the Control group (C), the LPS-treated group (L), and the IFN-τ + LPS-treated group (F). The results showed that there were 109, 1109, and 962 Differentially Expressed mRNAs (DEmRNAs) in the C vs L, C vs F, and L vs F. Gene Ontology (GO) and Kyoto Encyclopedia of Genes and Genomes (KEGG) enrichment analysis showed that these DEmRNAs were mainly involved in the regulation of host immune responses (e.g., NOD-like receptor signaling pathway, IL-17 signaling pathway and RIG-I-like receptor signaling pathway, NF-kappa B signaling pathway), signal transduction molecules and interactions (e.g., Cytokine-cytokine receptor interaction; Cell adhesion molecules), metabolic process (e.g., Glycosphingolipid biosynthesis-lacto and neolacto series) and Antigen processing and presentation, Complement and coagulation cascades, Th17 cell differentiation, etc. biological process. This study not only elucidates the molecular mechanisms by which BENDs respond to microbial invasion but also reveals the specific regulatory network through which IFN-τ exerts its anti-inflammatory effects via multiple synergistic pathways. It provides crucial theoretical support for the clinical application of interferon therapy in treating endometritis, demonstrating significant research value and promising applications.